Integrated online supervision and data management system / Siti Aishah Che Kar ... [et al.] - Che Kar, Siti Aishah; Ismail, Syila Izawana; Abdullah, Rina; Fadzal, Nazuha; Mohamed ©Omar, Hasiah (2018)
The use of online management systems has been progressively developed and adopted by most management in higher learning institutions, schools, and office in the public and private sectors as well as in business management. The developed system can facilitate all process management and thereby benefit many organizations and individuals involved. But before applying a system, usability testing should be made so that all the problems and errors can be identified prior to implementation. This paper analyzes the survey results about the usability of an online management system which is being developed: Online Project Evaluation and Supervision System (oPENs). Currently the system has partially developed a few processes in managing FYP such as submission of project approval forms, weekly reporting management process, and group registration process. For the next step, response from system users is needed so that this system can be completed by better fulfilling the features required by all users in addition to identifying problems that could arise before this system is implemented. To identify the system performance and to obtain lecturers’ responses about this system, a usability test is carried out where lecturers need to explore the system practically and answer the questionnaire in the end. There are three usability testing components that have been highlighted in the survey questions i.e. system appearance and interface, user-friendliness and system efficiency. During the system testing, Think Aloud method has been applied whereby the respondents are free to give any comment or suggestion for the system improvement. Most of the respondents strongly agree that this developed system can assist in the FYP supervisory process and also greatly assist coordinators in ensuring the FYP process runs smoothly. There is also a few suggestions that has been listed for the system’s improvement.